Transformasi BUMDes Melalui Community Based Tourism dalam Pengembangan Pariwisata: Studi pada Desa Sekapuk, Kabupaten Gresik - Isa , Muhammad Fatihuddin; Tamrin, M. Husni; Kudus , Imanudin (Indonesian Journal Publisher, 2024)
The study investigates the process of transformation of the village owned enterprise agency (BUMDes) into a community-based tourism development centre (CBT) in Sekapuk village, Gresik district. The research method used is case studies with a qualitative approach, involving in-depth interviews with stakeholders and analysis of related documents. The theory used is the concept of CBT as a community-based approach to local tourism development. The key findings suggest that active public involvement in all stages of tourism development, from planning to implementation, has significant economic, social, and environmental impacts. This implies that the CBT approach can be an effective model in strengthening the role of local communities in the development of sustainable tourism. The transformation of BUMDes into a CBT hub not only empowers local communities, but also ensures the sustainability of tourism initiatives by leveraging local resources and knowledge. The study's conclusions emphasize the importance of strengthening public capacity in tourism management, diversification of products and services, as well as government policy support for community-based tourism development. Implications of the research highlighted the need for advanced research to evaluate the long-term impact of this model and expand its application by considering local contexts and building strong partnerships among all relevant stakeholders.